2021
DOI: 10.1016/j.paid.2021.111038
|View full text |Cite
|
Sign up to set email alerts
|

What factors underlie attitudes regarding protective mask use during the COVID-19 pandemic?

Abstract: Two studies examine psychological and demographic factors that predict attitudes toward mask-wearing during the COVID-19 pandemic. These studies differentiate pro-mask from anti-mask attitudes. Political conservatism, younger age, and gender predicted anti-mask attitudes but were unrelated to pro-mask attitudes. Psychological reactance was associated with anti-mask attitudes, over and above demographic variables. Empathy, trust in healthcare professionals, and perceived normativity of mask wearing were associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
65
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(65 citation statements)
references
References 53 publications
0
65
0
Order By: Relevance
“…To inform our assessment of this convergence between interests of groups of publics on health issues, we draw on previous literature about mandatory vaccination policies, from psychology and behavioural science to ethics, political theory, sociology, and public policy. Very recently a literature on attitudes to mask-wearing has developed through psychologists, interested in knowing the factors that drive use [21] , including by demographic group (men vs women) [33] , [19] , as well as political scientists and public health researchers focused on mask messaging [40] and culture change [26] . Through this paper we aim at understanding how social media discussions and debates about mandates from mask-wearing to vaccination were connected through their opposition to COVID-19 public health policies and have evolved over the course of the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…To inform our assessment of this convergence between interests of groups of publics on health issues, we draw on previous literature about mandatory vaccination policies, from psychology and behavioural science to ethics, political theory, sociology, and public policy. Very recently a literature on attitudes to mask-wearing has developed through psychologists, interested in knowing the factors that drive use [21] , including by demographic group (men vs women) [33] , [19] , as well as political scientists and public health researchers focused on mask messaging [40] and culture change [26] . Through this paper we aim at understanding how social media discussions and debates about mandates from mask-wearing to vaccination were connected through their opposition to COVID-19 public health policies and have evolved over the course of the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…In many countries, wearing a mask is mandatory in certain public spaces (Adjodah et al, 2021 ). Although masks are effective in reducing person-to-person transmission (Adjodah et al, 2021 ; Eikenberry et al, 2020 ), many individuals have a negative view of mask-wearing (Mallinas et al, 2021 ). Such individuals are less likely to report following mask-wearing recommendations and mandates (Rieger, 2020 ) and may be more inclined toward other risky behaviors, such as preferentially seeking contact with non-mask wearers.…”
Section: Introductionmentioning
confidence: 99%
“…We, therefore, separated and identified likely mechanistic sources of county differences in response to subsequent COVID-19 waves. We predicted that the variance explained by both state and peer county group would increase during the pandemic as any uniformity in response to the early pandemic (if there was any to begin with) broke down along political and demographic lines [23, 19, 8]. Instead we found that peer county group was most important for the response between waves 1 and 2 but this importance decreased, replaced by state identity, between waves 2 and wave 3 (Figure 4, Table 1).…”
Section: Discussionmentioning
confidence: 99%